EXPERTISE AS PART OF PROFESSIONAL ACTIVITIES OF EDUCATION:THEORETICAL ASPECTST - Tryhub, Ilona I. (Educological discourse, 2014)
The article investigates the essence of the concept of «expertise». The author describes the areas of scientific expertise in the field of education and competences, which should have expertof education. The author believes that the task of providing scientific support to the development of education is essential for our country.